ChemInform Abstract: Development of 43Ca Solid State NMR Spectroscopy as a Probe of Local Structure in Inorganic and Molecular Materials. Issue 24 (2nd June 2014) - Laurencin, Danielle; Smith, Mark E.
Abstract Review: 156 refs.